2019
DOI: 10.1042/bsr20191124
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic initiation factor 3, subunit C silencing inhibits cell proliferation and promotes apoptosis in human ovarian cancer cells

Abstract: Ovarian cancer remains the leading cause of death among all gynaecological cancers, illustrating the urgent need to understand the molecular mechanisms involved in this disease. Eukaryotic initiation factor 3c (EIF3c) plays an important role in protein translation and cancer cell growth and proliferation, but its role in human ovarian cancer is unclear. Our results showed that EIF3c silencing significantly up-regulated 217 and down-regulated 340 genes. Ingenuity Pathway Analysis (IPA) indicated that the top di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, EIF3A, the largest subunit of EIF3 family, has been found to be abnormally overexpressed in a variety of malignant tumors, which may be a promising therapeutic target for the design of anti-cancer drugs 28 . EIF3C was also demonstrated to participate in the regulation of human cancers such as ovarian cancer 29,30 , renal cell carcinoma 31 , osteosarcoma 32 , and cervical cancer 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, EIF3A, the largest subunit of EIF3 family, has been found to be abnormally overexpressed in a variety of malignant tumors, which may be a promising therapeutic target for the design of anti-cancer drugs 28 . EIF3C was also demonstrated to participate in the regulation of human cancers such as ovarian cancer 29,30 , renal cell carcinoma 31 , osteosarcoma 32 , and cervical cancer 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxic melanoma EVs carried a hypoxic signature consisting of six proteins (AKR7A2, DDX39B, EIF3C, FARSA, PRMT5, VARS) which were significantly associated with a poor prognosis for melanoma patients. EIF3C promotes proliferation, migration and invasion of prostate [46], ovarian and hepatocellular carcinoma cells [47,48] and was associated with resistance to erlotinib in lung cancer [49]. PRMT5 (Protein arginine methyltransferase 5) is upregulated under hypoxia [50] and has many roles in cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…19 , 20 In addition, previous studies have demonstrated that inhibition of EIF3Cexpression can lead to inhibit cell proliferation and apoptosis. 21 , 22 However, the potential roles of EIF3Cin PC have not been fully understood.…”
Section: Discussionmentioning
confidence: 99%